A homolog of low molecular weight protein tyrosine phosphatase isolated from Brucella melitensis displays an acidic dual specific phosphatase activity, nonessential for bacterial resistance to bactericidal factors and virulence. (November 2022) - Zuo, Dong; Yin, Yi; Fang, Tian; Jiang, Hui; Ding, Jiabo; Hu, Hai; Wang, Shaohui; Qi, Jingjing; Tian, Mingxing; Yu, Shengqing
Abstract: Brucellosis is a bacterial infectious zoonosis which is spread worldwide, caused by Brucella, with infertility and abortion in domestic animals. Protein-tyrosine phosphatase (PTPs) have been discovered in many kinds of bacterial species, which play crucial roles in many aspects, such as bacterial physiology and virulence. However, no PTPs have been identified in Brucella to date. Here, we identified a novel gene BM28_RS15985 in Brucella melitensis that encodes a homolog of a low weight molecular PTP. Enzyme activity analysis showed that this PTP is a dual specific phosphatase, removing phosphate group from phosphotyrosine and phosphoserine/phosphothreonine peptides, which was designated as Dsp1. The optimal pH of the Dsp1 enzyme activity were 5.5, suggesting that the Dsp1 is an acidic phosphatase, and the optimal reaction temperature of the Dsp1 was 35.0 °C. Besides, the Michaelis constant and maximum reaction velocity of the Dsp1 were 40.17 mM and 24.33 nM/min/mg, respectively. In further study, we investigated the role of Dsp1 in B. melitensis phenotype and virulence. Growth curve and resistance test exhibited that the dsp1 had no role in Brucella growth and resisting bactericidal factors. Cell and animal infection experiment showed that the dsp1 deletion did not affect the intracellular survival and virulence of B. melitensis. In summary, we identified a novel acidic dual specific phosphatase in B. melitensis and evaluated its characteristics of the enzyme activity, this study will expand the understanding of Brucella phosphatase. Highlights: An acidic protein phosphatase Dsp1 in B. melitensis was identified. Dsp1 displayed a dual specific phosphatase activity. Dsp1 is not essential for Brucella resistance and virulence.